STUDY OF PART EFFICIENCIES OF THE HEAT EMISSION SYSTEM USING ROOM CFD-MODEL - ДЕШКО, В. І.; СУХОДУБ, І. О.; ЯЦЕНКО, О. І. (Technologies and Engineering, 2023)
Purpose. Determination of the part efficiencies of the heat emission system using CFD modeling of a typical room. Methods. The data used to calculate the part efficiencies of the heat emission were obtained in accordance with the methodology presented in DSTU B A.2.2-12:2015 (methodology based on EN 15316-2-1) and CFD modeling results. The k-ε (k-epsilon) turbulence model and the S2S (surface to surface) radiation model were used for modeling. Results. According to the results of numerical simulations, an analysis of the temperature distribution in the room was carried out. On the basis of the received data on the heat load of the room, the internal average volume and average radiation temperatures, as well as the temperature in the working area, the coefficients that take into account the influence of “over temperature” and specific heat losses through external enclosing structures were calculated for over-temperature of 29 K. Scientific novelty. The approach to determination of coefficients that take into account the influence of over temperature and specific heat losses through external enclosing structures was proposed. Therefore, the heat losses and the part efficiencies of the heat emission system coefficients given in DSTU B A.2.2-12:2015 can be specified using CFD-modeling. The practical significance. The given research results prove the feasibility of using CFD models to clarify heat losses when calculating heating system losses and, in particular, the heat-emitting component of this system. The presented results also make it possible to carry out a scientific justification of a number of values given in the tables of the standard DSTU B A.2.2-12:2015 (Annexes of the Standard EN 15316-2-1), which characterize the efficiency of the heat emission system.